If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 70 = 6x + -14 Reorder the terms: 70 = -14 + 6x Solving 70 = -14 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 70 + -6x = -14 + 6x + -6x Combine like terms: 6x + -6x = 0 70 + -6x = -14 + 0 70 + -6x = -14 Add '-70' to each side of the equation. 70 + -70 + -6x = -14 + -70 Combine like terms: 70 + -70 = 0 0 + -6x = -14 + -70 -6x = -14 + -70 Combine like terms: -14 + -70 = -84 -6x = -84 Divide each side by '-6'. x = 14 Simplifying x = 14
| 7j-4=3j-28 | | 10e-4=4e-10 | | 2a+4=-3a-36 | | -2q+6=3q-24 | | 2x-1=-x-28 | | 6h-4=h-9 | | 9y-1=5y+15 | | 12+8=5d+57 | | 7(3g+8)/4=35 | | 8-32x+27x-3=0 | | 4(x-5)=-1.6 | | 12d+8=8d+16 | | 13=5c-9 | | 9e-7=28.1 | | 8(x-2)=26.4 | | 2(3y-6)=-18 | | 2(7v-4)=-22 | | 3(4k-4)=60 | | 4(6u-4)=152 | | 3(5t+2)=-84 | | 5(4q+3)=-145 | | 8e-7=17 | | 16.2=2c-2 | | 5(4x-4)=-40 | | 3(4f+1)=-21 | | 5(3s-2)=-145 | | 6e-4=14 | | 9(a+3)=108 | | 2p=19.4 | | -3n+5=20 | | 6=3c-9 | | 7e-7=21 |